Ovulation induction and controlled ovarian stimulation using letrozole gonadotropin combination: A single center retrospective cohort study. (November 2017) - Arya, Sushila; Kupesic-Plavsic, Sanja; Mulla, Zuber D.; Dwivedi, Alok K.; Crisp, Zeni; Jose, Jisha; Noble, Luis S.
Abstract: Objective: To assess the effect of letrozole in combination with low dose gonadotropins for ovulation induction in anovulatory infertility from polycystic ovary syndrome (PCOS) and controlled ovarian stimulation for endometriosis, and unexplained infertility patients. Study design: Retrospective cohort study in a setting of private Reproductive Endocrinology and Infertility Clinic affiliated with the University. Three hundred couples (650 cycles) requiring OI/COS for PCOS (92 patients, 195 cycles), endometriosis (89 patients, 217 cycles), and unexplained infertility (119 patients, 238 cycles). Patients received 2.5 mg or 5 mg letrozole for 5 days (D3–D7) and recombinant follicle-stimulating hormone on alternating D3-D7 and human menopausal gonadotropin-highly purified alternating D5-D10 until growth of ideally 2 mature follicles. Ovulation was triggered with 10, 000 IU of HCG. Maximum number of cycles per patient was four. Results: Main outcome measures were clinical pregnancy rates, multiple order pregnancy rates, miscarriage rates, number of follicles and endometrial thickness on the day of HCG administration. The cumulative incidence of pregnancy was estimated as 35% (95%CI: 29%–41%) overall and was highest in patients with PCOS (36.6%), followed by unexplained infertility (34.6%) and endometriosis (32.5%). The pregnancy rates per cycle in PCOS, endometriosis and unexplained infertility patients were 17%, 13.2% and 17.2% respectively, no statistically significant difference between the groups. There were three twin pregnancies in PCOS, and one in unexplained infertility group. Monofolliculogenesis was noted in 48% of patients. Conclusion(s): Letrozole-low dose gonadotropins combination appears to be effective across different causes of infertility for superovulation. The letrozole-low dose gonadotropin combination resulted in high rate of monofolliculogenesis, low occurrence of multiple gestations and no case of OHSS or cycle cancellation.